Aircraft and tower measurements of CO2 concentration in the planetary boundary layer and the lower free troposphere over southern taiga in West Siberia: Long‐term records from 2002 to 2011. Issue 16 (30th August 2013) - Sasakawa, M.; Machida, T.; Tsuda, N.; Arshinov, M.; Davydov, D.; Fofonov, A.; Krasnov, O.
Abstract: [1] In situ measurements of the vertical distribution of carbon dioxide (CO2 ) carried out with a light aircraft over a tower site (Berezorechka; 56°08′45″N, 84°19′49″E) in the taiga region of West Siberia from October 2001 to March 2012 document the detailed seasonal and vertical variation of CO2 concentrations during daytime. The variation appears to be controlled mainly by the CO2 flux from taiga ecosystems and the height of the planetary boundary layer (PBL). We calculated average CO2 concentrations in the PBL and the lower free troposphere (LFT), both of which show clear seasonal cycles and an increasing long‐term trend. Seasonal amplitude in the PBL had a larger value (29 ppm) than that in the LFT (14 ppm), demonstrating strong CO2 source‐sink forcing by the taiga ecosystems. Mean CO2 concentrations during 13:00–17:00 local standard time observed at the four levels of the tower (5, 20, 40, and 80 m) showed lower CO2 concentrations than that observed in the PBL by aircraft during June–August (growing season). This negative bias decreased with increasing inlet height such that the minimum difference appeared at the 80‐m inlet (−2.4 ± 0.8 ppm). No such bias was observed during other months (dormant season). The daytime CO2 flux, based on multiple vertical profiles obtained on a single day, ranged from −36.4 to 3.8 µmol m −2  s −1 during July–September. There was a clear difference in the fluxes between the morning and afternoon, suggesting that these data should be considered examples of fluxes during several daytime hours from the West Siberian taiga. Key Points: Ten years of CO2 data from aircraft and tower observations in West Siberia Tower CO2 data in the afternoon could produce representative values for the PBL The most strongly negative CO2 fluxes were observed in the evening in July